Put the steps in order that are used to solve the following systems of equations by substitution.

−7x−2y=−13 and x−2y=11

x-2y=11--> x=2y+11
-7(2y+11)-2y=13
-16y=64,(3,-4)
x=3, x-2(-4)=11
-16-77=-13
y=-4
x+8=11
-14y-77-2y=-13

7 answers

1. Rearrange one of the equations to solve for one variable in terms of the other.
2. Substitute the value obtained in step 1 into the other equation.
3. Solve the resulting equation for the remaining variable.
4. Substitute the value obtained in step 3 into one of the original equations to solve for the other variable.
5. Repeat steps 1-4 for any additional variables.
6. Check the solution by substituting the values obtained in the original equations and verifying that they satisfy each equation.
put the numbers in order
1. x-2y=11
2. x=2y+11
3. -7(2y+11)-2y=13
4. -16y=64
5. y=-4
6. x+8=11
7. -14(-4)-77-2(-4)=-13
8. (3, -4)
10 steps
1. Rearrange the first equation to solve for x in terms of y: x = 2y + 11
2. Substitute the value of x from step 1 into the second equation: (2y + 11) - 2y = 11.
3. Simplify the equation from step 2: 11 = 11.
4. Since the equation in step 3 is always true, the system of equations has infinitely many solutions.
5. There is no need to solve for the values of x and y further.
6. The system of equations is consistent.
7. The equations describe a dependent system.
8. The graph of the equations is a line.
9. The graph of the equations intersects at every point along the line.
10. The system of equations is not overdetermined or underdetermined.
wrong
I apologize for the confusion. Here are the correct steps in order to solve the given system of equations by substitution:

1. Start with the given equations:
-7x - 2y = -13 (Equation 1)
x - 2y = 11 (Equation 2)

2. Solve Equation 2 for x in terms of y:
x = 2y + 11

3. Substitute the expression for x (from step 2) into Equation 1:
-7(2y + 11) - 2y = -13

4. Simplify the equation from step 3:
-14y - 77 - 2y = -13

5. Combine like terms:
-16y - 77 = -13

6. Add 77 to both sides of the equation:
-16y = 64

7. Divide both sides of the equation by -16:
y = -4

8. Substitute the value of y (from step 7) into Equation 2 to find x:
x - 2(-4) = 11

9. Simplify the equation from step 8:
x + 8 = 11

10. Subtract 8 from both sides of the equation:
x = 3

Therefore, the solution to the system of equations is:
x = 3
y = -4